Influence of Monitoring Tools on Project Performance in Kenyan State Corporations - Wanjala, Muchelule Yusuf; Iravo, Mike Amuhaya; Odhiambo, Romanus; Shalle, Noor Ismail (European Scientific Journal, ESJ, 2017)
The main objective of this study was to investigate the influence of monitoring tools on project performance of Kenyan State Corporations. Simple random sampling was used to select 65 state corporations that constituted the sample size. Data were collected from the sample size using questionnaires with both open and closed questions and they were administered by the researcher through a drop and pick technique. The collected data was analyzed using descriptive and inferential statistics as well as qualitative methods. The relationships between variables were determined using Pearson correlation and t-test. Assessments of normality were done by Shapiro-Wilk test while multicollinearity was detected by use of variation inflation factor (VIF). The study revealed that monitoring tools had no significant effect on project performance in Kenyan State Corporations (β2= 0.073, p>0.05). there is also a possibility that the monitoring tools were unable to map out the needed steps to attain the desired project results.